High‐speed based adaptive beamforming handover scheme in LTE‐R. Issue 10 (21st May 2018) - Zhao, Junhui; Liu, Yunyi; Wang, Chuanyun; Xiong, Lei; Fan, Lisheng
Abstract : In recent years, high‐speed railways (HSRs) are being developed rapidly all over the world because of their convenience, safety, comfort, and other advantages. However, the reliability and security of HSR wireless communication systems have faced severe challenges, such as the Doppler effect, complicated wireless channel model, frequent handovers and so on. The International Union of Railways is pushing the evolution of the global system for mobile communications for railway (GSM‐R) internationally. In this study, a high‐speed based adaptive beamforming handover scheme is proposed to improve the handover performance for HSR wireless communication systems. When the high‐speed train enters the overlapping region, the serving evolved NodeB (eNodeB) and target eNodeB are using beamforming with different gain factors to improve the received signal quality. In addition, this scheme can dynamically adjust the handover hysteresis margins of the reference signal receiving power (RSRP) and the reference signal receiving quality (RSRQ) based on the speed and position. Simulation results have demonstrated that the proposed handover scheme can improve the handover performance by increasing the handover trigger probability and success probability effectively.